2022
DOI: 10.1111/jne.13196
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 on the management of neuroendocrine tumors (NETS): An international NET CONNECT survey of NET patients and healthcare professionals treating net patients

Abstract: The COVID-19 outbreak has added complexity in the management of patients with neuroendocrine tumors (NETs). Little information is currently available regarding the real impact of the pandemic in current practice. The present study aimed to capture patients' and healthcare professionals' experiences on how the NET management has changed during the pandemic and how it should be modified in a foreseeable postpandemic environment. Physicians and nurses working in ENETS Centers of Excellence or other hospitals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Challenges posed by personalised care: As care becomes increasingly personalised during follow‐up, the impact of language, literacy, financial and cultural barriers on care‐seeking behaviours, 39 mental health and, ultimately, clinical outcomes of people living with NENs is amplified. These challenges have been exacerbated by the COVID‐19 pandemic, which had adverse effects on the mental health of people living with NENs 55,124–128 . A 2020 survey found that people undergoing longer‐term follow‐up for NENs experienced greater anxiety and decreased psychosocial wellbeing during the pandemic, as well as a greater reluctance to seek out care 124 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges posed by personalised care: As care becomes increasingly personalised during follow‐up, the impact of language, literacy, financial and cultural barriers on care‐seeking behaviours, 39 mental health and, ultimately, clinical outcomes of people living with NENs is amplified. These challenges have been exacerbated by the COVID‐19 pandemic, which had adverse effects on the mental health of people living with NENs 55,124–128 . A 2020 survey found that people undergoing longer‐term follow‐up for NENs experienced greater anxiety and decreased psychosocial wellbeing during the pandemic, as well as a greater reluctance to seek out care 124 .…”
Section: Resultsmentioning
confidence: 99%
“…These challenges have been exacerbated by the COVID-19 pandemic, which had adverse effects on the mental health of people living with NENs. 55,[124][125][126][127][128] A 2020 survey found that people undergoing longer-term follow-up for NENs experienced greater anxiety and decreased psychosocial wellbeing during the pandemic, as well as a greater reluctance to seek out care. 124 Maggie's Centres and NCUK provide free counselling and psychotherapy services to help people with NENs talk through their concerns, including finances, treatments and MDT care.…”
Section: -Hydroxyindoleacetic Acid Can Indicate a Biochemical Respons...mentioning
confidence: 99%